A másik hidegháború - Dávid, Ferenc (Afrika Tanulmányok / Hungarian Journal of African Studies, 2012)
Dávid Ferenc a következő művet mutatta be: Kilford, Christopher R.: The Other Cold War: Canada’s Military Assistance to the Developing World 1945-1975. Canadian Defence Academy Press, Kingston, 2010